2013
DOI: 10.1002/pmic.201200502
|View full text |Cite
|
Sign up to set email alerts
|

Proteome analysis reveals antiangiogenic environments in chronic wounds of diabetes mellitus type 2 patients

Abstract: In contrast to normal healing wounds, chronic wounds commonly show disturbances in proteins regulating wound healing processes, particularly those involved in cell proliferation and protein degradation. Multidimensional protein identification technology MS/MS was conducted to investigate and compare the protein composition of chronic diabetic foot exudates to exudates from split-skin donor sites of burn victims otherwise healthy. Spectral counting revealed 188 proteins differentially expressed (more than twofo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(84 citation statements)
references
References 43 publications
2
77
0
5
Order By: Relevance
“…Exudates from diabetic wounds studied by mass spectrometry revealed an increased expression of proteins with antiangiogenic properties [ 57 ] . Disturbed angiogenesis leads to hypoxia and subsequently cell death due to apoptosis or necrosis [ 57 ] .…”
Section: Angiogenesis and Vasculogenesis In Chronic Woundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exudates from diabetic wounds studied by mass spectrometry revealed an increased expression of proteins with antiangiogenic properties [ 57 ] . Disturbed angiogenesis leads to hypoxia and subsequently cell death due to apoptosis or necrosis [ 57 ] .…”
Section: Angiogenesis and Vasculogenesis In Chronic Woundsmentioning
confidence: 99%
“…Roughly 15-25 % of diabetics will develop a diabetic foot ulcer, which represents one of the most common complications, and accounts for more than 80 % of all lower leg amputations [ 56 ] . Exudates from diabetic wounds studied by mass spectrometry revealed an increased expression of proteins with antiangiogenic properties [ 57 ] . Disturbed angiogenesis leads to hypoxia and subsequently cell death due to apoptosis or necrosis [ 57 ] .…”
Section: Angiogenesis and Vasculogenesis In Chronic Woundsmentioning
confidence: 99%
“…However, in the case of chronic wounds, the normally-ischemic wound environment becomes even harsher, with excessive inflammation 100 and an environment not conducive to angiogenesis compared with normal wounds. 81 Therefore, a significant barrier to successful use of MSCs in any potential cell therapy has been post-implant cell survival in a variety of ischemic injury models. Past studies have shown marginal MSC preservation in various models including cardiac infarct 101 or cerebral injury, 102 but still MSC use in any of these models is limited by MSC death due to the harsh wound environment.…”
Section: Promotion Of Msc Survivalmentioning
confidence: 99%
“…Chronic wounds are often subject to antiangiogenic conditions, including reduced growth factor production as a result of increased MMP production in the wound bed, as outlined by Krisp et al recently in a global secretome analysis of wound exudates. 81 MSCs naturally produce a variety of pro-angiogenic factors following recruitment to the wound bed that stimulate endothelial cell proliferation and tube formation in the wound bed, most notably VEGF, a potent stimulator for angiogenesis that is regulated by IL-6 and TGF-α in the wound bed. 82 Though it has been shown that exogenous VEGF application to wounds can stimulate angiogenesis, 83 MSCs used in cell therapeutics also have been shown to stimulate EC recruitment and wound healing via VEGF secretion 33,75 or via pre-differentiation into angiogenic precursors.…”
Section: Stimulation Of Angiogenesismentioning
confidence: 99%
“…Such approaches are used to generate hypotheses that need to be verified in animal models and in humans [9]. So far, proteomics has been rarely used to discover new aspects of the delayed diabetic wound healing process, and the resulting pathways have never been validated [10][11][12]. Furthermore, cross-sectional comparisons of diabetic vs non-diabetic wound tissues have been biased by patients' differences and underlying conditions [10,11].…”
Section: Introductionmentioning
confidence: 99%